Outcome-based education (OBE) in ESP course: evaluation and students' feedback and performance - Rashid Ali, Farrah Diebaa (University Publication Centre (UPENA), 2009)
This paper examined students' feedback on the implementation of OBE in English for Accounting course. A total of 149 Bachelor of Accounting students participated in this study. A structured questionnaire was used to elicit students' feedback on their understanding relating to the course contents and fulfillment of course objectives.